EFFECT OF HIGH INTENSITY INTERVAL TRAINING ON THE CARDIOVASCULAR SYSTEM AND CARDIAC ANTI-AGING - Dharmasanti, Olivia (Sport and Fitness Journal; Vol 9 No 2 (2021): Volume 9, No. 2, May 2021, 2021)
Abstract   There are several risk factors leading to the development and progression of CVD, but one of the most prominent is a sedentary lifestyle. A healthy lifestyle can be characterized by both obesity and consistently low levels of physical activity. Lifestyle interventions that aim to increase physical activity and decrease obesity are attractive therapeutic methods to combat most non-congenital types of CVD. Aging is the another major risk factor for cardiovascular diseases (CVD), which are the leading cause of death in the United States. Epidemiological studies clearly show that aging itself is the major risk factor for cardiovascular and cerebrovascular diseases. Most of the research efforts on prevention of these diseases have ignored the mechanisms underlying cardiac and vascular effects of aging, and have focused, instead, on the development of interventions that target conventional cardiovascular risk factors. High-intensity interval training (HIIT) is frequently used in sports training. The effects on cardiorespiratory and muscle systems have led scientists to consider its application in the field of cardiovascular diseases. HIIT is defined as high intensity exercise for a defined period of time interspersed with rest periods (moderate light intensity or complete rest). This literature review was conducted to determine the correlation between high intensity interval training with the cardiovascular system and cardiac anti-aging.   Keywords: Cardiac anti-aging, cardiovascular system, cardiovascular disease, high intensity interval training.